Distribution and species diversity of freshwater crabs of the family Pseudothelphusidae in Colombia (Crustacea: Decapoda: Brachyura) - Campos,Martha R. (2020)
Abstract The study of Colombian freshwater crabs has advanced significantly, but species records are scattered across different museums and research institutions. Assuming that museum collections incorporate valuable information in estimating species diversity, a database was organized on the 94 known species of family Pseudothelphusidae, which includes 568 records from 1853 to 2019 in continental Colombia and Gorgona Island. The natural regions of Colombia (Amazonian, Andean, Caribbean, Orinoquian, Pacific) were further subdivided into 75 natural sub-regions according to habitat types used by freshwater crabs. Sub-regions were (i) ranked in terms of species richness, with respective species reported in each sub-region listed accordingly, and (ii) classified into a scale of five categories on the basis of a geometric biodiversity index combining species richness and Simpson index. Species accumulation curves are presented to estimate the current status of knowledge about the diversity of the Colombian pseudothelphusids. Although the available data are not standardized for an adequate assessment of relative abundance, since they are influenced by sampling efforts and natural sub-regions are of different sizes and characteristics, the present study may be useful in future ecological and biogeographic research, as well as for conservation purposes.